As representações do corpo humano nos livros didáticos de ciências - de Lima Soares, Emerson; Carrazoni Lopes Viçosa, Cátia Silene; Castro Pessano, Edward Frederico; Folmer, Vanderlei (Góndola, enseñanza y aprendizaje de las ciencias, 2018)
Several authors have pointed out that Didactic Book still plays an important role in the teaching and learning process, and is often the main, and the only educational resource available to teachers. In this way, we will analyze human body representations in Didactic Books of science adopted by a municipal public school in the city of Uruguaiana/RS. In the context of writing, we understand that body's perceptions permeate a historical and cultural construction, constituted from the relationships lived by the subjects in society. This study is a qualitative research, based on the content analysis of Bardin, in which we seek to identify human body representations in the messages, characteristics, structures, contents, and figures present in books. We set up an analytical matrix with guiding questions related to the approach of the body, showed in didactic books. The results demonstrate that the contents follow the same pattern: a body divided into parts like a human body just formed by limbs, organs, and tissues. They present a detailed division of content, from the cellular organization, concepts, structures, and the images are presented in a fragmented way, always following normative standards. We found these books dedicate spaces to analyze and discuss the biosocial body, in a well-elaborated way, contemplating different visions, such as sexuality beyond human reproduction. We believe that these issues should be part of the Political Education Projects (PPPs) of schools and the educational system as a whole because in this way more projects will be carried out contemplating the issue. However, it is still up to the teacher to take this approach, and if such issues are not addressed in the LD, he should keep in mind that if we are thinking beings, our body is much more than organic components, and so seek means to carry out this approach.